Private Law and Human Rights: New Realities - Ткалич, Максим Олегович; Ткалич, М. О.; Tkalych, Maxym О.; Сафончик, Оксана Іванівна; Сафончик, О. І.; Сафончик, Оксана Ивановна; Safonchyk, Oksana I.; Толмачевська, Юлія Олегівна; Толмачевська, Ю. О.; Толмачевская, Юлия Олеговна; Tolmachevska, Yuliia O. (Universidad Cooperativa de Colombia, 2020)
Point of view: One of the basic concepts that underlies law as a phenomenon, as well as private law as one of the two areas of law, is the concept of natural law. This concept presupposes that rights and freedoms are an inalienable good of every person, regardless of the will of any external institutions. The ideas of natural law have been expressed in the concept of private law (the fundamental principles of private law are such principles as justice, good faith, reasonableness, dispositiveness, legal certainty, inadmissibility of interference in private affairs, inviolability of property rights, and freedom of сontract). Object: The subject of the study is the problems of reforming of private law in modern conditions. The object of research is the social relations that arise in the plane of «person-person» and «state-person» in modern transformation processes. Methodology: The research methodology is formed by methods of analysis, synthesis, and modeling. Additionally, logical-legal, comparative-legal forecasting methods are used. The authors of the article tried to draw a parallel between the concepts of natural law, Roman law and private law. Results and discussion: An analysis of these concepts revealed that each of them is an integral part of the concept of modern Western civilization. At the same time, in modern conditions of pandemic, deglobalization, regionalization, collapse of human rights and the very concept of Western civilization, which is based on the ideas of humanism, liberalism, absolute human rights, inviolability of property rights and respect for privacy, are under threat.

Однією з основних концепцій, яка лежить в основі права як явища, а також приватного права як однієї з двох галузей права, є концепція природного права. Ця концепція передбачає, що права та свободи є невід'ємним благом кожної людини, незалежно від волі будь-яких зовнішніх установ. Ідеї ​​природного права були виражені в концепції приватного права (основними принципами приватного права є такі принципи, як справедливість, добросовісність, розумність, диспозитивність, юридична визначеність, неприпустимість втручання в приватні справи, недоторканість прав власності та свобода договору). Предметом дослідження є проблеми реформування приватного права в сучасних умовах. Об'єктом дослідження є соціальні відносини, що виникають у площині «людина-людина» та «держава-людина» в сучасних трансформаційних процесах. Методологія дослідження формується методами аналізу, синтезу та моделювання. Додатково застосовуються логіко-правові, порівняльно-правові методи, методи прогнозування. Автори статті намагалися провести паралель між поняттями природного права, римського права та приватного права. Аналіз цих концепцій показав, що кожна з них є невід’ємною частиною концепції сучасної західної цивілізації. Водночас у сучасних умовах пандемії, деглобалізації, регіоналізації, краху прав людини і самої концепції західної цивілізації, яка базується на ідеях гуманізму, лібералізму, абсолютних прав людини, недоторканності прав власності та поваги до приватного життя , знаходяться під загрозою.

Одной из основных концепций, которая лежит в основе права как явления, а также частного права как одной из двух отраслей права, является концепция естественного права. Эта концепция предусматривает, что права и свободы являются неотъемлемым благом каждого человека, независимо от воли любых внешних учреждений. Идеи естественного права были выражены в концепции частного права (основными принципами частного права являются такие принципы, как справедливость, добросовестность, разумность, диспозитивность, юридическая определенность, недопустимость вмешательства в частные дела, неприкосновенность прав собственности и свобода договора). Предметом исследования являются проблемы реформирования частного права в современных условиях. Объектом исследования являются социальные отношения, возникающие в плоскости «человек-человек» и «государство-человек» в современных трансформационных процессах. Методология исследования формируется методами анализа, синтеза и моделирования. Дополнительно применяются логико-правовые, сравнительно-правовые методы, методы прогнозирования. Авторы статьи пытались провести параллель между понятиями естественного права, римского права и частного права. Анализ этих концепций показал, что каждая из них является неотъемлемой частью концепции современной западной цивилизации. В то же время в современных условиях пандемии, деглобализации, регионализации, краха прав человека и самой концепции западной цивилизации, основанной на идеях гуманизма, либерализма, абсолютных прав человека, неприкосновенности прав собственности и уважения к частной жизни, находятся под угрозой.
Tkalych M. Private Law and Human Rights: New Realities / M. Tkalych, О. Safonchyk, Y. Tolmachevska // DIXI. – V. 22 (2). – Universidad Cooperativa de Colombia, 2020. – Р. 11-12.
Keywords: dispositive method of legal regulation; imperative method of legal regulation; natural law; private law; Roman law; диспозитивний метод правового регулювання; імперативний метод правового регулювання; природне право; приватне право; римське право; диспозитивный метод правового регулирования; императивный метод правового регулирования; естественное право; частное право; римское право; Research Subject Categories::LAW/JURISPRUDENCE